Unruptured distal anterior cerebral artery mirror aneurysms associated with ruptured middle cerebral artery aneurysm: case report - Jovanović, Vladimir; Rasulić, Lukas; Kovačević, Vojin Stevo; Janićijević, Aleksandar Miloš; Vitošević, Filip; Savić, Andrija; Đurović, Marko; Tasić, Goran (Vojnosanitetski pregled, 2021)
Introduction: Mirror ACA aneurysms are rare, especially in the absence of any congenital vascular anomaly. Case report: We present a 49-year-old woman with diagnosed unruptured distal anterior cerebral artery (ACA) mirror aneurysms, associated with ruptured right middle cerebral artery (MCA) aneurysm. A ruptured MCA aneurysm was previously coiled in other neurosurgical center, while the mirror distal ACA aneurysms were clipped through right-sided unilateral craniotomy in our Institution. Conclusion: There are no clear recommendations regarding the follow-up and management of unruptured distal ACA aneurysms, but they should be aggressively treated even if they are small, due to their tendency for early rupture and high incidence of intracerebral bleeding. Single stage unilateral craniotomy is recommended for surgical treatment.